2010
DOI: 10.1007/s10562-010-0285-4
|View full text |Cite
|
Sign up to set email alerts
|

3-(2-Hydroxyl-Ethyl)-1-Propylimidazolium Bromide Immobilized on SBA-15 as Efficient Catalyst for the Synthesis of Cyclic Carbonates via the Coupling of Carbon Dioxide with Epoxides

Abstract: 3-(2-hydroxyl-ethyl)-1-propylimidazolium bromide (HEPIMBr) was immobilized onto SBA-15, Al-SBA-15 mesoporous molecular sieves and SiO 2 by chemical grafting method. The materials were characterized and used as catalysts for solvent-free synthesis of cyclic carbonates from CO 2 and epoxides under relatively mild conditions. Among them, the HEPIMBr immobilized on SBA-15 performs the best, showing carbonate selectivity and yield of ca. 100% (120°C, 2.0 MPa, 2 h). The catalyst is thermally stable and shows good re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 61 publications
4
40
0
Order By: Relevance
“…Zhu et al [32] reported that the molecular sieve-supported choline chloride/urea exhibited good catalytic activity, but urea was indispensable. We also fabricated hydroxyl ionic liquid catalyst immobilized SBA-15 molecular sieve, and found it showed good catalytic activity towards the coupling reaction [35]. But its reusability is not satisfactory, similar to the ionic liquid catalysts immobilized on MgO, SiO 2 , or MCM-41 [27,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [32] reported that the molecular sieve-supported choline chloride/urea exhibited good catalytic activity, but urea was indispensable. We also fabricated hydroxyl ionic liquid catalyst immobilized SBA-15 molecular sieve, and found it showed good catalytic activity towards the coupling reaction [35]. But its reusability is not satisfactory, similar to the ionic liquid catalysts immobilized on MgO, SiO 2 , or MCM-41 [27,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Although, this catalyst is active at relatively lower temperature, i.e., 353 K, the selectivity for the cyclic carbonate was reported to be less because of the formation of diol by-products. A number of groups have reported imidazoliumbased ionic liquids supported on mesoporous silica [21], commercial silica surfaces [22], SBA-15 [23] and polymers [24,25] as effective catalysts for this transformation. Most importantly, these catalysts are not active without the halide anions present in the ionic liquids.…”
Section: Introductionmentioning
confidence: 99%
“…ILs immobilized on mesoporous sieves (SBA-15 [78,79] and MCM-41 [80][81][82]) and polymeric materials [83,84] could act as efficient catalysts for the transformation of CO 2 into cyclic carbonates with high yield and excellent selectivity under relatively mild conditions. High activity is displayed when ILs immobilized on carboxymethyl cellulose (CMC) and chitosan (CS) are applied as heterogeneous catalysts for cycloaddition of epoxides with CO 2 , since CMC or CS is rich in hydroxyl and carboxyl groups [85][86][87].…”
Section: Supported Ionic Liquidmentioning
confidence: 99%